2017
DOI: 10.1097/mlr.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Alternative Care Site Characteristics Into Estimates of Substitutable ED Visits

Abstract: Alternative care sites vary widely in operating hours and functional capabilities. Methods such as ours may help incorporate this variability into estimates of ED visit substitutability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…In the complex health care landscape of the United States, EDs occupy a unique position and have been the focus of a number of interventions and studies to assess their use, particularly for low-acuity conditions that could potentially be treatable elsewhere (Ragin et al, 2005; Trueger et al, 2017). Our study finds that gaining Medicaid coverage under the ACA shifts previously uninsured patients toward using the ED for conditions that were more likely to result in hospital admission and in admissions for nonambulatory sensitive conditions than the same patients had been using the ED for previously, compared to trends for those who remained uninsured in nonexpansion states.…”
Section: Discussionmentioning
confidence: 99%
“…In the complex health care landscape of the United States, EDs occupy a unique position and have been the focus of a number of interventions and studies to assess their use, particularly for low-acuity conditions that could potentially be treatable elsewhere (Ragin et al, 2005; Trueger et al, 2017). Our study finds that gaining Medicaid coverage under the ACA shifts previously uninsured patients toward using the ED for conditions that were more likely to result in hospital admission and in admissions for nonambulatory sensitive conditions than the same patients had been using the ED for previously, compared to trends for those who remained uninsured in nonexpansion states.…”
Section: Discussionmentioning
confidence: 99%
“…25 Beyond these attributes, services offered in an urgent care center can vary widely, from primary care to less common offerings, such as occupational medicine, weight loss, and physical therapy services. 25,30 Though data limitations have made it difficult to conduct research on urgent care centers, there is a slightly more establishedalbeit mixed-literature on retail clinics, for which data are more readily available. Retail clinics differ from urgent care centers in that they are located within a retail location (rather than operating as stand-alone entities), are much more limited in number, are primarily staffed by nurse practitioners (rather than MDs), treat a smaller set…”
Section: The Urgent Care Marketmentioning
confidence: 99%
“…The emergency department (ED) is a commonly utilized health care setting for many Americans when unexpected health challenges arise 1 . Although vital, the ED is viewed as an expensive site of care, especially for conditions that could be managed in less resource‐intensive settings 2 . Prior estimates have suggested that a sizable proportion of ED visits are for low‐acuity complaints that could be treated in cheaper alternatives, such as urgent care (UC) centers or retail clinics 2 .…”
Section: Variables Seven‐state Sample Low‐acuity Users (N = 1986) Prmentioning
confidence: 99%
“…Although vital, the ED is viewed as an expensive site of care, especially for conditions that could be managed in less resource‐intensive settings 2 . Prior estimates have suggested that a sizable proportion of ED visits are for low‐acuity complaints that could be treated in cheaper alternatives, such as urgent care (UC) centers or retail clinics 2 . Over the past decade, these alternatives to the ED for unexpected, low‐acuity visits have rapidly emerged in the market 3 .…”
Section: Variables Seven‐state Sample Low‐acuity Users (N = 1986) Prmentioning
confidence: 99%
See 1 more Smart Citation